2014
DOI: 10.4315/0362-028x.jfp-14-162
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to Antimicrobial Agents among Salmonella Isolates Recovered from Layer Farms and Eggs in the Caribbean Region

Abstract: This investigation determined the frequency of resistance of 84 isolates of Salmonella comprising 14 serotypes recovered from layer farms in three Caribbean countries (Trinidad and Tobago, Grenada, and St. Lucia) to eight antimicrobial agents, using the disc diffusion method. Resistance among isolates of Salmonella was related to the country of recovery, type of sample, size of layer farms, and isolate serotype. Overall, all (100.0%) of the isolates exhibited resistance to one or more of seven antimicrobial ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 31 publications
3
10
0
Order By: Relevance
“…This occurrence of a high frequency of multidrug resistance reported in this study, in addition to the occurence of a total of 18 multi-resistance patterns, demonstrate a potential for the likelihood of chemotherapeutic failure that may be connected with the use of these antimicrobials in the area. These findings corroborate the report on Salmonella isolates from poultry by other researchers (Ahmed et al, 2017, Adesiyun et al, 2014a, Oluwasile et al, 2014, Elmadiena et al, 2013, Mir et al, 2010.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…This occurrence of a high frequency of multidrug resistance reported in this study, in addition to the occurence of a total of 18 multi-resistance patterns, demonstrate a potential for the likelihood of chemotherapeutic failure that may be connected with the use of these antimicrobials in the area. These findings corroborate the report on Salmonella isolates from poultry by other researchers (Ahmed et al, 2017, Adesiyun et al, 2014a, Oluwasile et al, 2014, Elmadiena et al, 2013, Mir et al, 2010.…”
Section: Resultssupporting
confidence: 93%
“…(2014a) which reported a prevalence of (59.5%) among Salmonella isolates from poultry farms in three Caribbean countries, however, it is much higher when compared to other results from poultry studies which ranges from 0.0 to 17% (Oluwasile et al, 2014, Snow et al, 2007. The frequency of resistance to streptomycin detected in the current study (60.3%) corroborates with 21.9 to 92.9% previously reported for poultry farms (Adesiyun et al, 2014a, Enabulele et al, 2010. The fact that frequency of resistance was statistically significant to streptomycin, gentamicin, nalidixic acid and compound sulfurnamide in Ilorin south, Ilorin west, Irepodun and Asa Local Government areas respectively suggest possible misuse of the antimicrobials in the areas and therefore, there is need for concern authorities to promulgate policy that will regulate the use of antimicrobials in the areas and the country at large.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…A more recent study investigated the presence of antibiotic resistant genotypes of Salmonella isolated from broiler hens found that more than 43% of the isolates were resistant to ampicillin, amoxicillin-clavulanic acid, ceftiofur, cefoxitim, and ceftriaxone [ 37 ]. This was supported by Adesiyun et al [ 38 ] who isolated 84 isolates of Salmonella from egg productions processes in Trinidad and Tobago, Grenada, and St. Lucia and found that all of the 84 isolates displayed resistance to one or more of the seven antimicrobial agents tested. A high frequency of resistance was observed against erythromycin, streptomycin, gentamycin, kanamycin, ampicillin, and tetracycline.…”
Section: Production Control Measuresmentioning
confidence: 68%
“…It is very significant by virtue of the fact that, it can be transmitted vertically from parent to offspring; this makes its control a challenge. Although vaccination and good hygiene practices are most effective ways to prevent salmonellosis (11), antibiotics are extensively using either as a growth promoter or prophylaxis and therapeutics in poultry industry of Bangladesh (12, 13). Indeed, the widespread misapplication and nonjudicious use of antimicrobial drugs in poultry settings, culminating the development of antimicrobial resistant pathogens like Salmonella (Gyles, 2008, Cantas et al, 2013; Antunes et al, 2016).…”
Section: Introductionmentioning
confidence: 99%